2002
DOI: 10.1149/1.1481065
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Structural and Electrochemical Properties of Superstoichiometric Ti-Zr-V-Mn-Cr-Ni Hydrogen Storage Alloys

Abstract: In this paper, the structural and electrochemical properties of the superstoichiometric (Ti 0.8 Zr 0.2 )(V 0.533 Mn 0.107 Cr 0.16 Ni 0.2 ) x ͑x ϭ 2, 3, 4, 5, 6͒ hydrogen storage alloys have been studied systematically. It is found by X-ray diffraction and energy dispersive spectra analysis that all these alloys mainly consist of two phases, a C14 Laves phase with hexagonal structure and a V-based solid solution phase with body-centered cubic structure. The lattice parameters and thus the cell volumes of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 26 publications
1
55
0
1
Order By: Relevance
“…When the overpotential is changed within a small range, the polarisation resistance R p can be estimated from the slope of the linear polarisation curve. Then the I 0 is calculated from the value of R p according to Equation (1). The obtained values of I 0 and R p are summarised in Table 5.…”
Section: High-rate Dischargeability (Hrd) and Electrochemical Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the overpotential is changed within a small range, the polarisation resistance R p can be estimated from the slope of the linear polarisation curve. Then the I 0 is calculated from the value of R p according to Equation (1). The obtained values of I 0 and R p are summarised in Table 5.…”
Section: High-rate Dischargeability (Hrd) and Electrochemical Kineticsmentioning
confidence: 99%
“…[1][2][3] Besides the merits of higher energy density, higher charge and discharge ability, and longer charge/discharge cyclic life, the Ni-MH battery also has a smaller memory effect and causes less environmental pollution compared with the rechargeable nickel-cadmium battery. [4][5][6] To date, almost all commercial Ni-MH batteries employ AB 5 type alloys as negative electrode materials because of their good overall electrode properties.…”
Section: Introductionmentioning
confidence: 99%
“…Takahashi [1,2] reported that hydrogen storage alloys, V 3 TiNi 0.56 and V 3 TiNi 0.56 Hf 0.24 had higher discharge capacity than AB 5 type alloy and Ti 22 V 66 Ni 12 had discharge capacity up to 800 mAh g )1 at 293 K. Thereafter, the properties of TiV 2.1 Ni x alloy electrodes were studied and it was shown that this negative electrode had higher discharge capacity than the above-mentioned alloy [3,4]. Pan et al [5,6] studied (Ti 0.8 Zr 0.2 )(V 0.533 Mn 0.107 Cr 0.16 Ni 0.2 ) (x=2, 3, 4, 5, 6, 7) multiphase hydrogen storage electrode alloys and pointed out that the alloys had good cycling stability and high rate dischargeability at 303 K. Up to now, the influence of temperature on the discharge capacity of the multiphase alloy has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…[7] However, the electrochemical capacity of the AB 5 -type alloys is limited by the single CaCu 5 -type hexagonal structure; [8] the energy densities of the Ni-MH batteries cannot compete favorably with some other advanced secondary batteries. Therefore, new types of alloys with higher energy densities, faster activation, better rate dischargeabilities, and lower cost are urgently needed to replace the conventional rare-earth-based AB 5 -type alloys. [9] charge current density of 1200 mA/g, the high-rate dischargeability of the alloy electrodes increases linearly from 47.2 % (x = 0) to 73.8% (x = 0.8).…”
Section: Introductionmentioning
confidence: 99%